Web-Based Caries Risk Assessment and Parental Feedback: A Cross-Sectional Implementation Study of Tegal's IDCRA School Program - Erma Sofiani; Indri Kurniasih; Frida Arba Martadewi; Saskia Sabrina Putri; Cahyani; Agus Dwi Sulistyantono (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Dental caries remains a major public health issue among Indonesian children, driven by poor oral hygiene and limited parental awareness. This study describes the use of the Indonesian Digital Caries Risk Assessment (IDCRA) as a web-based screening tool and parent-reporting platform. Methods: This study employed a cross-sectional quantitative design, involving 227 students and their parents from both public and private elementary schools in Tegal, Central Java. Data were collected through dental screenings and parent feedback. Only 130 of 227 parents responded (57.3%). An analysis included descriptive statistics, validity-reliability tests, and Mann-Whitney and Chi-Square tests. Ethical approval was obtained from the Ethics Committee of the Faculty of Medicine and Health Sciences at Universitas Muhammadiyah Yogyakarta (FKIK UMY). All participants provided informed consent to ensure their rights were protected. Results: Private-school students had higher mean of DEF.T (Decayed, Extracted, Filled Teeth) scores compared to public school (4.91 +/- 3.6 vs 1.97 +/- 2.8; Mann-Whitney U = 9699.500; p < 0.001; r = 0.45). However, DMF.T scores (Decayed, Missing, Filled Teeth) did not differ significantly (1.75 +/- 2.7 vs 2.09 +/- 2.6; U = 5824.500; p = 0.200; r = 0.09). Among the parents, perceptions of the digital report and support for school-based oral health program were generally favorable. No statistically significant differences between school types across the questionnaire items. Conclusion: This study demonstrates the feasibility of a locally developed IDCRA as a digital platform for school-based dental screening and communication of oral health findings to parents in the participating schools. The findings support further longitudinal and controlled evaluation of whether digital reporting leads to sustained care-seeking behavior, improved oral hygiene supervision, and reduced caries burden.